2021
DOI: 10.4102/sajip.v47i0.1877
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic organisational capabilities: The role of authentic leadership and trust

Abstract: Orientation: The world of work has become unstable and precarious, thereby accentuating the need to maintain dynamic capabilities such as sensing, seizing and reconfiguring to adapt and thrive. Associated challenges potentially threaten the well-functioning of organisations and their employees. This problem might be alleviated by encouraging the leaders to be more authentic, resulting in various positive outcomes.Research purpose: The aim of the study was to assess the associations authentic leadership (AL) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…In turn, a high level of AL skills allows people to create a positive work environment. This is confirmed by research [ 17 , 18 , 39 , 40 , 41 ]. Similar observations were also made in relation to nurses [ 14 , 15 , 42 , 43 , 44 ], as well as for nurses starting work [ 45 ].…”
Section: Discussionsupporting
confidence: 83%
“…In turn, a high level of AL skills allows people to create a positive work environment. This is confirmed by research [ 17 , 18 , 39 , 40 , 41 ]. Similar observations were also made in relation to nurses [ 14 , 15 , 42 , 43 , 44 ], as well as for nurses starting work [ 45 ].…”
Section: Discussionsupporting
confidence: 83%
“…The positive relationship between organizational support and trust strengthens the conclusion reached by Zeng et al (2020) that support as a resource generates positive emotions – in this study, trust – among employees. Additionally, Kleynhans et al (2021a) mention that leaders who are open and allow employees to get to know them instill trust in the organization.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Chen and Sriphon (2022) indicated that authentic leadership was linked positively to both social exchange relationships and trust. Furthermore, an authentic leadership style can promote a healthy and supportive work setting characterized by sound relationships and trust among team members, follower trust in their leaders ( Asad et al, 2021 ), and in their organization ( Miniotaite and Buciuniene, 2013 ; Alkaabi, 2018 ; Kleynhans et al, 2021a ). It is thus plausible to argue that increased levels of trust can be ascribed to the example set by authentic leaders who are characterized by high moral standards, honesty, transparency, and integrity.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…It is a futile exercise if the accumulated knowledge is not rightly embedded in the organizational capabilities. Thus, it is imperative to strengthen the firm's ability to exploit/seize opportunities for the pursuit of superior performance (Kleynhans et al, 2021; Morgan et al, 2012; Nuruzzaman et al, 2019; Sheng, 2017).…”
Section: Introductionmentioning
confidence: 99%